Механические характеристики наноструктурированных циркония и цирконий-ниобиевых сплавов - Соколенко, В.И.; Мац, А.В.; Мац, В.А. (Физика и техника высоких давлений, 2013)
В цирконии и его сплавах с ниобием путем холодной прокатки сформировано наноструктурное состояние с оптимальной конфигурацией замкнутых границ и определены механические характеристики исследуемых материалов. Приведены результаты испытаний на растяжение и данные микротвердости образцов из Zr и сплавов Zr−1% Nb и Zr−2.5% Nb в исходном состоянии и после прокатки при 293 K на степень ε = 3.9. Полученное наноструктурное состояние в каждом материале обеспечивает наряду с высокой прочностью достаточный запас пластичности. В связи с этим в работе рассматривались не только дислокационно-дисклинационные механизмы формирования наноструктуры, но и особенности пластического течения с эволюцией наноструктуры при растяжении в диапазоне равномерной деформации. У Zr і сплавах Zr−1% Nb і Zr−2.5% Nb шляхом холодної прокатки сформовано наноструктурний стан з оптимальною конфігурацією замкнутих меж і визначено механічні характеристики. Представлено результати випробувань на розтягування й дані мікротвердості зразків у вихідному стані й після прокатки при 293 K на ступінь ε = 3.9. Отриманий наноструктурний стан в досліджених матеріалах забезпечує разом з високою міцністю достатній запас пластичності. У роботі розглядалися не лише дислокаційно-дисклінаційні механізми формування наноструктури, але й особливості пластичної течії з еволюцією наноструктури під час розтягування у діапазоні рівномірної деформації. The work is aimed at formation of a nanostructural state with optimal configuration of contour boundaries in zirconium and Zi–Nb alloys by cold rolling and estimation of mechanical characteristics of the tested materials. The results of the tensile tests and microhardness measurements of the Zr, Zr–1%Nb, Zr–2.5%Nb samples before and after rolling at 293 K to the degree of ε=3.9 are given. The obtained nanostructural state provides sufficient degree of plasticity combined with high strength in every material. Thus, the work considered not only dislocation and disclination mechanisms of nanostructure formation but peculiarities of plastic flow with nanostructure evolution at tension within the range of uniform deformation. The tests have demonstrated a possibility of creation of a nanostructural state in industrial Zr–Nb alloys with using a certain mode of rolling that does not allow crack formation and fracture of the material. The kinetics of formation of the majority of boundaries is mostly of dislocation nature, not the result of dynamic polygonization and recrystallization. The resistance to plastic deformation is determined by amount, energy and nature of deformation boundaries. The effect of the general increase in mechanical characteristics in the course of nanograin formation reduces the level of brittle fracture more than in the case of high-strength state.